Biomarkers in molecular medicine: cancer detection and diagnosis - Padma Maruvada; Wendy Wang; Paul D. Wagner; Sudhir Srivastava (BioTechniques)
In spite of advances in diagnostics and therapeutics, cancer remains the second leading cause of death in the U.S. Successful cancer treatment depends not only on better therapies but also on improved methods to assess an individual's risk of developing cancer and to detect cancers at early stages when they can be more effectively treated. Current cancer diagnostic imaging methods are labor-intensive and expensive, especially for screening large asymptomatic populations. Effective screening strategies depend on methods that are noninvasive and detect cancers in their early stages of development. There is increasing interest and enthusiasm in molecular markers as tools for cancer detection and prognosis. It is hoped that newly discovered cancer biomarkers and advances in high-throughput technologies would revolutionize cancer therapies by improving cancer risk assessment, early detection, diagnosis, prognosis, and monitoring therapeutic response. These biomarkers will be used either as stand-alone tests or to complement existing imaging methods.